Therapeutic effect of omega‐3 fatty acids on T cell‐mediated autoimmune diseases. (15th June 2020) - Ouyang, Liu; Dan, Yang; Hua, Wenbin; Shao, Zengwu; Duan, Deyu
Abstract: The present study was to demonstrate that the G protein coupled receptors serve as targets for the treatment of autoimmune disease such as rheumatoid arthritis and multiple sclerosis. Rats received pristane at the base of the tail. Affected joints were counted daily. The T cell mediated autoimmune diseases such as pristine‐induced arthritis (PIA) and autoimmune encephalomyelitis (EAE) in a rat model were profoundly ameliorated by treatment with the specific G protein couple receptors 120 (GPR120) stimuli omega‐3 fatty acids (ω‐3 FAs). Our study further revealed that the activation of GPR120 by ω‐3 FAs can result in a decrease of phosphorylated transforming growth factor‐β activated kinase 1 (TAK1), and further inhibit the downstream IKKβ/I‐κB pathway and the terminal NF‐κB activation which serves as a mediator of T cell activation. ω‐3 Fatty acids exhibited an inhibitory effect on TAK1 by enhancing the association of β‐arrestin2 and TAK1 binding protein 1 (TAB1), thus the disassociation of TAB1 from the TAB1/TAK1 complex renders a limited effect on β‐arrestin2 signaling as an innate immunity regulation. GPR120 is a functional receptor of ω‐3 fatty acids in T cell‐mediated autoimmune disease compared with its effect on innate immunity.